INTRODUCTION OF CASE-BASED LEARNING IN PHYSIOLOGY AND EVALUATION OF THE LEARNING EXPERIENCE - Dhillon, Sukhjinder Kaur; Thaman, Richa Ghay; -, Kiran; Sandhu, Parminder; Arora, Dimple Bajaj (Pakistan Journal of Physiology, 2018)
Background: Case-based learning (CBL) is a long established pedagogical method, which is defined in a number of ways depending on the discipline and type of ‘case’ employed. Basic, social, and clinical sciences are studied in relation to the case, integrated with clinical presentations and conditions, and student learning is, therefore, associated with real life situations. This study was done to explore, analyse and synthesise the evidence relating to the effectiveness of CBL as a means of achieving defined learning outcomes in health professionals’ education. Methods: The study was conducted in the Department of Physiology SGRDIMSAR, Amritsar India. Faculty and students were sensitised about the case-based learning. An overview about Thyroid and Pancreatic gland was given to students in didactic lectures. Paper-based case scenarios of goitre and diabetes were given to students. Then during the tutorial time cases were discussed in small groups, and one teacher acted as facilitator for each small group. After that, feedback was taken from the students and faculty using five point Likert scale. Statistical analysis was done using SPSS-14. Students were assessed with the help of MCQs after each module. Results: Ninety-six percent of students thought that CBL was an effective learning tool for them, and 91% opined that it improved their analytical abilities. Most (96%) students reported that CBL helps in better retention of knowledge, 93% thought the cases were appropriate to the lecture topics and 89% wanted to have more CBL sessions. Seventy-seven percent students thought that CBL improved their communication and collaborative skills and ability to work within a team. Regarding faculty perception of CBL, 86% took CBL better than conventional method, it promoted self-study and problem solving abilities (90%), recall and application of basic sciences to clinical scenario (84%), improved communication skills of students (78%), and felt that it should be done regularly. Conclusions: Majority of the students enjoy CBL and think that it enhances learning. The empirical data taken as a whole is conclusive as to the effects on learning compared with other types of activity. Teachers enjoy CBL, partly because it engages, and is perceived to motivate students. CBL seems to foster learning in small groups. Whether this is the case delivery or the group learning effect, is unclear. Pak J Physiol 2016;12(3):9–12